An unusual pressure sore, can the head ring be implicated? - K. Rajan; R. Dias; N. Dave; D. Galante; I. Chincoli (Pediatric Anesthesia and Critical Care Journal (PACCJ))
Many injuries sustained during anaesthesia may be avoided through anticipation and high standards of cli- nical practice. These critical incidents causing minor in- juries occur more commonly than they are reported, may cause severe pain and suffering and are often the subject of medical litigation. However no protective strategy is completely effective and continuous vigilan- ce in procedures involving extreme positioning is war- ranted.